Konsep Informasi Dalam Perspektif Islam - Irma Damayanti; Erwan Efendi; Rony Pernando Sagala (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this study is to analyze the important role of information systems in an Islamic view, so that humans can apply them in social life. The type of method used in this study is a qualitative method using valid data. The results of this study indicate that in applying the concept of information in an Islamic perspective, information is disseminated in a factual and honest manner and in accordance with the teachings of the Islamic religion. In learning information systems, the concept of information is very important and useful as a good means and method of conveying information in accordance with Islamic teachings. The dissemination of information in the application of this information concept contains a lot of knowledge for people to know what is needed in an information system, then to know what are the characteristics of an information concept, as well as the components needed in an information system. Keywords: Information, System, Islam